2005
DOI: 10.1603/0022-0493-98.2.595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of Sorghum Genes Expressing Tolerance to Damage by Greenbug (Homoptera: Aphididae)

Abstract: Genetic linkage maps are fundamental for the localization of genes conferring tolerance to greenbug, Schizaphis graminum (Rondani), feeding damage in sorghum, Sorghum bicolor (L.) Moench. Thirteen linkage groups (LGs) containing 60 simple sequence repeat (SSR) loci were mapped by using a set of sorghum recombinant inbred lines (RILs) obtained from the cross '96-4121' (greenbug-tolerant parent) x Redlan (greenbug-susceptible parent). The LG spanned a distance of 603.5 cM, with the number of loci per LG varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Out of the nine sorghum loci detected for all four biotypes (C, E, I and K), three loci conferred resistance for biotype I. These loci were located on SBI05(LGH), SBI06(LG D), SBI07(LGJ) for biotype I and one loci on SBI09(LG G) accounted for resistance to biotypes C and E. Nagaraj et al (2005) identified three QTLs for biotype I resistance and five QTLs for biotype K resistance. For the biotype I, there were two QTLs present on chromosomes SBI01(LG5) and one on SBI04 (LG 3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Out of the nine sorghum loci detected for all four biotypes (C, E, I and K), three loci conferred resistance for biotype I. These loci were located on SBI05(LGH), SBI06(LG D), SBI07(LGJ) for biotype I and one loci on SBI09(LG G) accounted for resistance to biotypes C and E. Nagaraj et al (2005) identified three QTLs for biotype I resistance and five QTLs for biotype K resistance. For the biotype I, there were two QTLs present on chromosomes SBI01(LG5) and one on SBI04 (LG 3).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, linkage maps allow researchers to identify and tag significant genomic regions affecting traits such as insect resistance and disease resistance (Mohan et al 1997; Yencho et al 2000; Reddy et al 2008). Several linkage maps developed in sorghum have facilitated tagging of greenbug resistance (Agrama et al 2002; Katsar et al 2002; Nagaraj et al 2005; Wu et al 2007; Wu & Huang 2008; Punnuri et al 2013). The alleles accounting for sorghum biotype I resistance have been documented through quantitative trait loci (QTL) studies, which support the involvement of multiple regions of the sorghum genome in greenbug resistance (Agrama et al 2002; Katsar et al 2002; Nagaraj et al 2005; Wu & Huang 2008; Punnuri et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have been used to identify and characterize QTL associated with many different traits in sorghum, including plant height and maturity [57], traits associated with domestication [58], disease resistance, insect resistance [59], and drought tolerance. Identification of QTL often leads to further investigations to identify the underlying gene or genes through fine mapping and map-based cloning.…”
Section: Qtl Identification In Sorghummentioning
confidence: 99%
“…However, concerted efforts toward breeding for shoot fly resistance have resulted in some progress, and a number of genotypes with resistance to shoot fly have been identified (Sharma et al, 2003). The economic impact of shoot fly, the improvement of genetic resistance to this pest is one of the major goals of sorghum breeding programs in India (Nagaraj et al, 2005). The shoot fly resistance in sorghum appears to be a complex trait and depends upon the interaction of a number of component traits, which finally sum up in the expression of shoot fly resistance (Dhillon, 2005).…”
Section: Introductionmentioning
confidence: 99%